Search for pair production of excited top quarks in the lepton plus jets final state - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (SPRINGER, 2014)
A search is performed for pair-produced spin-3/2 excited top quarks , each decaying to a top quark and a gluon. The search uses data collected with the CMS detector from pp collisions at a center-of-mass energy of = 8 TeV, selecting events that have a single isolated muon or electron, an imbalance in transverse momentum, and at least six jets, of which one must be compatible with originating from the fragmentation of a b quark. The data, corresponding to an integrated luminosity of 19.5 fb(-1), show no significant excess over standard model predictions, and provide a lower limit of 803 GeV at 95% confidence on the mass of the spin-3/2 t(*) quark in an extension of the Randall-Sundrum model, assuming a 100% branching fraction of its decay into a top quark and a gluon. This is the first search for a spin-3/2 excited top quark performed at the LHC.
Keywords: Hadron-Hadron Scattering; Top physics; Physics